Prevalence of Helicobacter pylori among medical workers in Moscow and Kazan according to ¹³С-urease breath test - D. S. Bordin; R. G. Plavnik; V. I. Nevmerzhitskiy; L. I. Butorova; R. A. Abdulkhakov; S. R. Abdulkhakov; I. N. Voinovan; Iu. V. Embutnieks (Alʹmanah Kliničeskoj Mediciny, 2018)
Rationale: The relevance of the problem is related to the lack of data on Helicobacter pylori (HP) prevalence in Russia, which is associated with the risk of peptic ulcer and gastric cancer, and also, on the other hand, to the non-adherence of the doctors to the existing expert guidelines on diagnosis of this infection and HP eradication therapy.Aim: To assess the prevalence of HP among medical workers and their willingness to undergo eradication therapy.Materials and methods: A total of 315 medical workers (61 men and 254 women) aged 18 to 76 years were examined, among them 221 in Moscow and 94 in Kazan. To assess the HP contamination rate, all participants performed a ¹³С-urease breath test with the “HELICARB” test kit according to the “four-point” technique. All participants were asked to complete the questionnaires to access the impact of social and occupational factors on the prevalence of HP.Results: HP was identified in 54.9% of the examined subjects, including 45.9% of men and 57.1% of women. The prevalence of HP in Moscow was substantially lower (49.8%) than in Kazan (67%). The proportion of HP-positive subjects increased with age from 41.8% in those below 25 years of age to 76.9% in those above their 60s. 60.2% of married participants and 49% of the singles were HP-positive. Among doctors, HP prevalence rate was the largest in the endoscopy specialists (61.5%) and internists (60.9%). Only 61.4% of HP-positive medical workers expressed their willingness to undergo eradication therapy.Conclusion: The study showed a high prevalence of HР in medical workers increasing with age. It is presumably related to hygiene habits and conditions during childhood of each generation; however, one cannot exclude their potential contamination during their occupational activities.